2011
DOI: 10.1002/acp.1605
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative effects of physical context reinstatement on eyewitness recall and identification

Abstract: The impact of context reinstatement (CR) on eyewitness recall and identification was explored in this study. Participants viewed a video of a staged theft and, following a 1-week interval, were asked to identify the culprit and recall the event in either the same or in a different physical environment. Results suggested that CR enhanced the perceived familiarity of the lineup members, which in turn increased participants' willingness to identify someone in the lineup. Although CR significantly improved facial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Further, context reinstatement has been found to enhance participants' judgments of familiarity about individuals shown in a lineup, regardless of their identification accuracy (Sanders, 1984). Various other studies have found similar results (Wong & Read, 2011;Hanczakowski et al, 2014). Given these results, it was predicted that in the current study, participants in the matched context conditions would make fewer correct rejections (i.e., lower accuracy) with a target-absent lineup than those in the mismatched context condition.…”
Section: Context Reinstatement and Its Role In Memorysupporting
confidence: 47%
See 4 more Smart Citations
“…Further, context reinstatement has been found to enhance participants' judgments of familiarity about individuals shown in a lineup, regardless of their identification accuracy (Sanders, 1984). Various other studies have found similar results (Wong & Read, 2011;Hanczakowski et al, 2014). Given these results, it was predicted that in the current study, participants in the matched context conditions would make fewer correct rejections (i.e., lower accuracy) with a target-absent lineup than those in the mismatched context condition.…”
Section: Context Reinstatement and Its Role In Memorysupporting
confidence: 47%
“…Finally, the retrieval phase is the process in which previously stored information is either recalled or recognized. A change in contextual information at encoding and retrieval is one factor that can influence memory accuracy (Wong & Read, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations